2018
DOI: 10.1002/suco.201700235
|View full text |Cite
|
Sign up to set email alerts
|

Effect of parameters on the compressive strength of fly ash based geopolymer concrete

Abstract: Geopolymer concrete is an inorganic polymer composite which has the potential to build an eco‐friendly and sustainable construction by replacing the existing conventional concrete. Herein, cement is totally replaced by mineral admixtures rich in aluminosilicates such as fly ash and is formed by the alkali activation using alkaline activator solutions, such as sodium hydroxide (NaOH) and sodium silicate (Na2SiO3). Fly ash, a waste material from industry, can be incorporated in the manufacture of geopolymer conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
51
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 95 publications
(56 citation statements)
references
References 27 publications
(38 reference statements)
5
51
0
Order By: Relevance
“…It is categorized as a high energy‐intensive product which releases carbon dioxide (CO 2 ) into the atmosphere during its production . About 40% of CO 2 emissions are produced as a result of building‐related energy consumption and concrete made from ordinary Portland cement (PC) is second only to water as the most material used by mankind today and the cement production contributing for concrete product approximately 10% of global CO 2 emission in the near future . CO 2 emissions are mainly due to fossil fuel burning and limestone decomposition for cement production while grinding and transport are also essential factors in the environmental damage of the cement industry.…”
Section: Introductionmentioning
confidence: 99%
“…It is categorized as a high energy‐intensive product which releases carbon dioxide (CO 2 ) into the atmosphere during its production . About 40% of CO 2 emissions are produced as a result of building‐related energy consumption and concrete made from ordinary Portland cement (PC) is second only to water as the most material used by mankind today and the cement production contributing for concrete product approximately 10% of global CO 2 emission in the near future . CO 2 emissions are mainly due to fossil fuel burning and limestone decomposition for cement production while grinding and transport are also essential factors in the environmental damage of the cement industry.…”
Section: Introductionmentioning
confidence: 99%
“…Research findings over the past 10 years revealed that fresh and hardened properties of GP concrete were affected the composition of alkaline activators and their content relative to binding materials, aggregates contents, and sodium hydroxide molarity as well as curing temperature and period . The type and composition of base materials or their blend have crucial impacts upon the polymerization extent of GP composites, hence its internal structure .…”
Section: Generalmentioning
confidence: 99%
“…The above outlined literature works revealed that the potential of using OSA, as a base material in the production of GP composites, was merely investigated, if none . This work aimed at studying the potential of producing geopolymer mortar (GPM) using Jordanian OSA; considering inherent key parameters, namely concentration of catalysis materials, and alkaline/binder ratios; where the binder (B) represents the solid consistent of sodium hydroxide (NH), sodium silicate (NS), and OSA, and water represents the sum of water in alkaline solutions and water added to maintain consistency.…”
Section: Generalmentioning
confidence: 99%
“…Plastic shrinkage refers to the volume change due to the evaporation of water from the concrete paste in the fresh state during the hardening process, and drying shrinkage is caused by internal water evaporation from the matrix due to low external environmental humidity of the cement‐based materials after hardening of cement . For the last two decades, there have been numerous published studies on the use of admixtures as a supplementary cementitious material to improve the mechanical performance and resist shrinkage ability of concrete . It could be concluded that cement with admixtures has a lower permeability due to the formation of calcium silicate hydrate (C‐S‐H) than that of Portland cement .…”
Section: Introductionmentioning
confidence: 99%